Model Triple Helix in the Partnership of UNY, Industry, and Government for Research-Based Human Resource Development - Darmono Darmono; Heri Nurdiyanto; Nur Endah Januarti; Krisnanda Dwi Apriyanto (Utan Kayu Publishing, 2025)
This study explores the implementation of the Triple Helix model in strengthening research-based human resources through the strategic partnership between Universitas Negeri Yogyakarta (UNY), industry, and government. The Triple Helix framework posits that innovation and human capital development emerge from synergistic interactions among universities, industry, and government, each contributing unique resources, knowledge, and policy support. At UNY, this partnership is realized through collaborative research projects, technology transfer, curriculum alignment with industrial needs, and policy facilitation aimed at fostering employability and research competence of graduates. The university serves as a knowledge hub that generates research and innovation, while industries provide practical expertise, funding, and employment opportunities, and the government ensures regulatory support and incentives. This paper analyzes case studies of collaborative programs, highlighting mechanisms such as joint research centers, internships, scholarships, and community service initiatives that integrate research into human resource development. The findings demonstrate that the Triple Helix model fosters mutual benefits: UNY enhances its academic relevance and societal impact, industries gain access to skilled and innovative talent pools, and the government achieves policy goals related to national development and workforce competitiveness. The study also identifies challenges, including misaligned expectations, bureaucratic barriers, and funding sustainability, and proposes recommendations for strengthening the governance of partnerships and aligning stakeholder objectives. Overall, the research concludes that the Triple Helix partnership at UNY exemplifies a promising model for advancing research-based human resources that are adaptive, innovative, and responsive to dynamic industrial and societal needs. This model underscores the importance of sustained communication, trust, and shared vision among stakeholders to optimize the outcomes of such collaborations in the Indonesian context and beyond.